2003
DOI: 10.1097/00007632-200306010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Endplay assessment in and of itself did not contribute to the same-day pain and stiffness relief observed in neck pain patients receiving spinal manipulation. The impact on a longer course of treatment remains to be investigated. The data suggest that pain modulation may not be limited to mechanisms associated with manipulation of putative motion restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…If manual assessments of spinal stiffness are simply unreliable and invalid, their continued use during clinical examination is difficult to justify. This conclusion has been reached by several other authors after reviewing the reliability literature (Troyanovich et al 1998; Seffinger et al 2004) and is consistent with studies that find a lack of association between assessments of spinal motion and clinical outcomes (Chiradejnant et al 2003a; Haas et al 2003; Kanlayanaphotporn et al 2009). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…If manual assessments of spinal stiffness are simply unreliable and invalid, their continued use during clinical examination is difficult to justify. This conclusion has been reached by several other authors after reviewing the reliability literature (Troyanovich et al 1998; Seffinger et al 2004) and is consistent with studies that find a lack of association between assessments of spinal motion and clinical outcomes (Chiradejnant et al 2003a; Haas et al 2003; Kanlayanaphotporn et al 2009). …”
Section: Discussionsupporting
confidence: 89%
“…Several studies reported that choosing a manual therapy technique based on assessments of spinal stiffness results in no better outcomes than random selection (Chiradejnant et al 2003a; Haas et al 2003; Kanlayanaphotporn et al 2009). Moreover, as a part of a population-based study, Leboeuf-Yde et al (Leboeuf-Yde et al 2002) found that manual assessments of spinal stiffness were not helpful in differentiating people with and without LBP.…”
Section: Introductionmentioning
confidence: 99%
“…It may explain how target vs non-target site manual therapy interventions can show similar clinical efficacy. 13,6062 In a recent study using the same model as the current study, the increase in L 6 muscle spindle response caused by an HVLA-SM is not different between 3 anatomical thrust contact sites (spinous process, lamina, mammillary body) on the target L 6 vertebra but is significantly less when the contact site is located 1 segment caudal at L 7 (Reed et al submitted). The current study confirms that a non-target HVLA-SM compared to a target HVLA-SM decreases spindle response but adds the caveat that a substantial percentage (60–80%) of afferent response can be elicited from an HVLA-SM delivered 2 segments away irrespective of the absence or presence of intervertebral fixation.…”
Section: Discussionsupporting
confidence: 49%
“…To date, at least 2 randomized clinical trials involving HVLA-SM support the concept that while precise segmental level accuracy may be ideal, it is not an absolute prerequisite for clinical efficacy. 13,62 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even were they accurate, the information might prove to be of little clinical utility. An innovative efficacy study [29] using a randomized trial study design explored whether the data provided by MP was associated with a clinically relevant pain reduction in one session of cervical manipulation compared with non-specific cervical manipulation. Although the study found endplay assessment did not contribute to same-day clinical improvement in the cervical spine, the investigators did not rule out possible contribution over a longer term.…”
Section: Discussionmentioning
confidence: 99%